Between Rocks and Hard Places: Exploring the Impact of Structurational Divergence in the Nursing Workplace. (February 2013) - Nicotera, Anne Maydan; Mahon, Margaret M.
Recurrent interpersonal conflict in organizational settings is common and impedes goal-attainment. Structurational divergence (SD) theory conceptualizes a distinctive negative communication spiral rooted in unresolved conflict resulting from incompatible rules of intersecting meaning structures. This article expands SD theory by examining the function of human agency, positing that the rendering of communication patterns as incomprehensible and untransformable diminishes agency. After explaining and expanding SD theory, an exploratory study examines the relationship of SD to conflict-related organizational- and communication-related constructs. Destructive communication (verbal aggression, ambiguity intolerance, controlling conflict management style, and taking conflict personally) is related to SD whereas constructive communication (solution oriented conflict management style, argumentativeness) is not. Implications are discussed for understanding conflict in nursing and other organizational settings as well as for intervention.